(untitled) (Annals of Medical Research, 2023)
Aim: The aim of the present study is to determine inflammatory mediators that may be used in predicting in-hospital mortality in traumatic acute subdural hematoma (TASDH) patients and to evaluate their significance as prognostic markers. Materials and Methods: The medical records of adult patients with traumatic acute subdural hematoma admitted to the emergency department were reviewed retrospectively. The primary clinical outcome was in-hospital mortality. Univariate and multivariate Cox regression analyses were performed for the identification of independent predictors of in-hospital mortality. Besides, receiver operating characteristic (ROC) analysis was applied to determine the power of inflammatory mediators in predicting mortality. Results: According to the Cox hazard models, the mean platelet volume (MPV) /platelet count (PLT) ratio (MPR) (Hazard Ratio (HR) = 1.129; 95% CI = 1.059 – 1.204; p < 0.001), C-reactive protein (CRP)/lymphocyte ratio (CLR) (HR = 1.011; 95% CI = 1.002 – 1.020; p = 0.022) and C-reactive protein(CRP)/albumin ratio (CAR) (HR =1.004; 95% CI = 1.001 – 1.007; p = 0.004 were risk factors for in-hospital mortality. The results of ROC analysis indicated that the MPR of 0.06 or above predicted in-hospital mortality with 67% sensitivity and 88% specificity (p = 0.001). In addition, the CLR of 39.12 and above predicted in-hospital mortality with 63% sensitivity and 93% specificity and the CAR of 8.79 (p = 0.001) and above predicted it with 66% sensitivity and 87% specificity (p = 0.002) Conclusion: Increased MPR, CLR and CAR values are strong predictors of in-hospital mortality in TASDH patients.